Interact-2010 2010
DOI: 10.1109/interact.2010.5706143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface roughness using machine vision

Abstract: In this work, a machine vision system has been utilized to determine the surface roughness of the milled surfaces. For checking the effectiveness of the machine vision based results, a wide range of surface roughness were generated on CNC milling centre using Design of Experiments (DoE) technique. Stylusbased parameters Ra and Rsm were acquired and compared with vision-based parameters (Ga, R1, R2, CV, contrast etc). Model equations have been developed, in terms of the machining parameters, image parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…noticed in their experimental work that HFRC recorded lowest delamination factor and surface roughness when compared with glass, jute and banana fibre‐reinforced composites. They concluded that low feed rates coupled with high cutting speeds reduced delamination and prolonged tool life . Ogawa et al .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…noticed in their experimental work that HFRC recorded lowest delamination factor and surface roughness when compared with glass, jute and banana fibre‐reinforced composites. They concluded that low feed rates coupled with high cutting speeds reduced delamination and prolonged tool life . Ogawa et al .…”
Section: Introductionmentioning
confidence: 90%
“…Mechanical properties such as creep life, fatigue strength, wear, and corrosion resistance can be improved through a desirable quality drilled hole. Babu et al . noticed in their experimental work that HFRC recorded lowest delamination factor and surface roughness when compared with glass, jute and banana fibre‐reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…It is very common to measure the surface roughness in CNC machined parts by visual methods and compare them with conventional values, contact techniques such as; the arithmetic mean of the roughness (Ra) and spacing between peaks of the midline (Rsm), [9]. Additionally, the characterization can be done with 3D walls [10], and the use of neural networks [11].…”
Section: Related Workmentioning
confidence: 99%
“…It drastically reduces the assembly tolerances and strength against fatigue which later reducing and degrading the long term performance of the composite parts. Babu et al [8] stated that the natural fiber reinforced composites materials are recognized as better materials for structural applications, however, machining of these composites may causes a number of problems. Several damages for instance delamination, fiber pull-out, edge chipping, uncut fibers and others are some of the sources occurs in drilling of composite materials [9].…”
Section: Introductionmentioning
confidence: 99%